2005
DOI: 10.1080/0961321042000329422
|View full text |Cite
|
Sign up to set email alerts
|

Citizens' expectations of information cities: implications for urban planning and design

Abstract: The European Union has made the development of a vibrant knowledge-based economy a key policy objective, and increasingly national and local governments worldwide are seeking to harness information and communication technologies to provide government services more effectively and for the benefit of their citizenry. The paper reports on the first phase of the ongoing European Union IntelCities integrated project that seeks to integrate electronic governance of cities and urban planning. The background to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 5 publications
0
22
0
1
Order By: Relevance
“…The work developed by Capata, Marella and Russo (Capata et al 2008) aims to support decision making during crisis situations, while Convertino et al (Convertino et al 2008) was focused on emergency planning. Curwell et al (Curwell et al 2005) aimed at supporting urban planning. These works however are more spatial-oriented than decision-oriented.…”
Section: Synthesis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The work developed by Capata, Marella and Russo (Capata et al 2008) aims to support decision making during crisis situations, while Convertino et al (Convertino et al 2008) was focused on emergency planning. Curwell et al (Curwell et al 2005) aimed at supporting urban planning. These works however are more spatial-oriented than decision-oriented.…”
Section: Synthesis and Discussionmentioning
confidence: 99%
“…E-planning is the label adopted by a wide-ranging research agenda addressing the interaction between information technology and planning, including various key concerns such as territorial management, policy making, governance, citizenship and participation (Curwell et al 2005). Our mission was supporting a group of stakeholders (architects, urban designers, city planners, public administrators, and social and political scientists) collaboratively developing city plans.…”
Section: Introductionmentioning
confidence: 99%
“…doi:10. /j.ijinfomgt.2007 of the various stakeholders' interest in participation and the development of the technological infrastructure have resulted in many new projects designed to exploit the potential of ICT that supports communication and participation in political processes (Bekkers, 2004;Best & Krueger, 2005;Curwell, Deakin, Cooper, & Paskaleva-Shapira, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The respondents from developing countries indicated that this is exacerbated where IT accessibility is limited and does not reach rural areas, minorities and lower social groups. These issues of accessibility have been extensively documented (Bauer, Berne, & Maitland, 2002;Niles & Hanson, 2003;Oden & Lentz, 2001;Simpson, Daws, & Pini, 2004) as have the opportunities, limitations and challenges encountered when using computer technology (Charlton, Gittings, Leng, Little, & Neilson, 1999;Curwell et al, 2005;Merrick, 2003;Shiffer, 1995). Accessibility issues are of particular relevance in developing countries (Brooks, Donovan, & Rumble, 2005).…”
Section: The Potential Role Of It In Participative Processesmentioning
confidence: 99%